2021
DOI: 10.1590/0001-3765202120200774
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Structure and Magnetic Behavior of Zn-Doped Magnetite Aqueous Ferrofluids Prepared from Natural Sand for Antibacterial Agents

Abstract: This study performs natural sand-based synthesis using the sonochemical route for preparing Zn-doped magnetite nanoparticles. The nanoparticles were dispersed in water as a carrier liquid to form Zn-doped magnetite aqueous ferrofluids. Structural data analysis indicated that the Zn-doped magnetite nanoparticles formed a nanosized spinel structure. With an increase in the Zn content, the lattice parameters of the Zn-doped magnetite nanoparticles tended to increase because Zn 2+ has a larger ionic radius than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…In terms of antimicrobial activity, the available literature demonstrates the potential of both zinc/cerium-substituted magnetite nanoparticles and zinc/cerium oxide nanoparticles against a wide variety of microbial species, e.g., B. cereus [ 19 ], B. subtilis [ 24 , 60 ], S. aureus [ 20 , 32 , 60 , 61 , 62 ], S. enterica [ 63 ], E. coli [ 19 , 20 , 24 , 60 , 61 , 62 , 63 , 64 ], P. aeruginosa [ 60 , 65 ], C. jejuni [ 63 ], and C. albicans [ 19 ]. While the mechanistic pathway behind the activity of zinc/cerium-substituted magnetite nanoparticles has not been precisely determined, it could be assumed that it is based on the targeting of the microbial cell wall, followed by the release of the zinc and cerium ions within the microbial environment and the consequent generation of intracellular reactive oxygen species [ 31 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of antimicrobial activity, the available literature demonstrates the potential of both zinc/cerium-substituted magnetite nanoparticles and zinc/cerium oxide nanoparticles against a wide variety of microbial species, e.g., B. cereus [ 19 ], B. subtilis [ 24 , 60 ], S. aureus [ 20 , 32 , 60 , 61 , 62 ], S. enterica [ 63 ], E. coli [ 19 , 20 , 24 , 60 , 61 , 62 , 63 , 64 ], P. aeruginosa [ 60 , 65 ], C. jejuni [ 63 ], and C. albicans [ 19 ]. While the mechanistic pathway behind the activity of zinc/cerium-substituted magnetite nanoparticles has not been precisely determined, it could be assumed that it is based on the targeting of the microbial cell wall, followed by the release of the zinc and cerium ions within the microbial environment and the consequent generation of intracellular reactive oxygen species [ 31 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…While zinc ion concentrations are physiologically regulated through homeostasis to prevent excess cell uptake and toxicity, above optimum levels allow cell entry and cytotoxicity towards prokaryotes [ 20 ]. In this context, zinc can be used as an efficient inhibitor of bacterial and fungal strain growth [ 20 , 24 , 25 ]. Furthermore, numerous studies have reported the tumor suppressor effects of zinc, which generally involve the alteration of bioenergetic and metabolic mechanisms, inhibition of cell cycle activity and, consequently, of malignant advancement to metastasis and promotion of apoptosis [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation